The role of neisseria gonorrhoeae in oral cavity: a literature review - Piro, Sylvia C.A. de; Dias, Eliane P. (Brazilian Journal of Sexually Transmitted Diseases, 2002)
The changes in sexual bchavior. sexual rclations at an earlicr age and use of drogs are some of thc principal reasons for an increase in vcncreal disease. Gonorrhea is an infectious disease caused by a Gram-negativc intracellular diplococcus. Neisseria gonorrhoeae that have a prediiection for mucous membrane. Since thc gonococcus affecls primarily mucous membranc, it is surprising that thc membrane of lhe oral cavity are not mexe often infectcd. The oral cavity can be involved in a gonococca lnfeclion eithcr directly or indirectly. lhe aim of this study is describe lhe oral manifestations. diagnosis and treatment aspects for assist lhe dentist for a carly diagnostic.